Cellulose Valorization via Electrochemical Oxidation: Efficient Formate Generation for Green Energy Storage - Shuhan Xiao; Yang Yang (Biomass, 2025)
Achieving efficient electrocatalytic oxidation of cellulose-derived biomass is a pivotal strategy for advancing bioenergy utilization and achieving carbon neutrality. This study addresses the challenges of low conversion efficiency caused by cellulose’s high crystallinity and excessive energy consumption in conventional processes by proposing a novel integrated system combining solid heteropoly acid catalytic pretreatment and electrocatalytic oxidation. By preparing the (C16TA)H2PW solid acid catalyst, we successfully achieved hydrolysis of microcrystalline cellulose under 180 °C for 60 min, attaining a glucose yield of 40.1%. Furthermore, a non-noble metal electrocatalyst system based on foam copper (CuF) was developed, with the Co3O4/CuF electrode material demonstrating a Faradaic efficiency of 85.3% for formate production at 1.66 V (vs. RHE) in 1 mol L−1 KOH electrolyte containing the pretreated cellulose mixture, accompanied by a partial current density of 153.2 mA cm−2. The mechanism study indicates that hydroxyl radical-mediated C-C bond selective cleavage dominates the formate generation. This integrated system overcomes the limitations of poor catalyst stability and low product selectivity in biomass conversion, offering a sustainable strategy for green manufacturing of high-value chemicals from cellulose.